Modernization And Change In The Wool Industry In South Peru 1919-1930: A Frustrated Case Of Development - Bertram, Geoff (1977)
Recent discussions on the relationship between forms of capitalist production and "pre-capitalist" in Latin America have focused attention particularly on the penetration of capitalist forms in backward rural economies such as the Peruvian highlands. It is generally recognized that there are two basic ways in which capitalist penetration can occur: first, the integration of pre-capitalist sectors in a wider market through exchange relations, and second, transformation of the sector's own pre-capitalist to capitalist relations of production over large units of production, wage labor, investment in improvements for a rural capitalist class of entrepreneurs.